2014
DOI: 10.1021/ja412001e
|View full text |Cite
|
Sign up to set email alerts
|

Construction and Validation of Nano Gold Tripods for Molecular Imaging of Living Subjects

Abstract: Anisotropic colloidal hybrid nanoparticles exhibit superior optical and physical properties compared to their counterparts with regular architectures. We herein developed a controlled, stepwise strategy to build novel, anisotropic, branched, gold nanoarchitectures (Au-tripods) with predetermined composition and morphology for bioimaging. The resultant Au-tripods with size less than 20 nm showed great promise as contrast agents for in vivo photoacoustic imaging (PAI). We further identified Au-tripods with two p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
156
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 168 publications
(160 citation statements)
references
References 55 publications
3
156
0
1
Order By: Relevance
“…Different from conventional fluorescence or bioluminescence imaging techniques that are suitable mostly for small animals, PA imaging has already moved into clinical trials owing to its significantly improved in vivo imaging depth (as deep as ∼12 cm) and spatial resolution compared with traditional optical imaging modalities (10,11,13). A large variety of nanoscale agents, including both organic and inorganic ones, with absorption in the near-infrared (NIR) "tissue transparent" optical window have been extensively explored as PA imaging probes (14)(15)(16)(17)(18)(19)(20). For example, many types of nanoparticles with strong and constant NIR absorbance are often used for enhanced blood pool imaging and PA imaging of tumors (15,16,19).…”
mentioning
confidence: 99%
“…Different from conventional fluorescence or bioluminescence imaging techniques that are suitable mostly for small animals, PA imaging has already moved into clinical trials owing to its significantly improved in vivo imaging depth (as deep as ∼12 cm) and spatial resolution compared with traditional optical imaging modalities (10,11,13). A large variety of nanoscale agents, including both organic and inorganic ones, with absorption in the near-infrared (NIR) "tissue transparent" optical window have been extensively explored as PA imaging probes (14)(15)(16)(17)(18)(19)(20). For example, many types of nanoparticles with strong and constant NIR absorbance are often used for enhanced blood pool imaging and PA imaging of tumors (15,16,19).…”
mentioning
confidence: 99%
“…Similarly, pentapeptide-GNPs (CALNN and others) concentrated in the liver following intravenous injection in rats, again without any signs of toxicity 92 . Other in vivo studies conducted using cyclic-RGD-conjugated nanogold tripods 93 , RGD-gold nanorods 94 , VEGF-receptor binding peptide- 95 and adipose homing peptidefunctionalised GNPs 96 similarly did not reveal any evidence of toxicity or other adverse effects, although it should be pointed out that all these studies are relatively short-term. An in vivo study in mice of unfunctionalised GNPs indicated significant toxicity of nanoparticles in the size range 8-37nm however, interestingly, conjugation of immunogenic peptides to the GNPs reduced toxicity significantly 97 .…”
Section: Discussionmentioning
confidence: 88%
“…Theranostic AuNPs combine diagnosis with therapy of malignant cells in the same platform for convenient application in vitro and in vivo. However, the long-term cytotoxicity and immune 65 response existed in tumor treatment using AuNPs are still unsolved problems. Thus, improving functional design and exploiting new structure of AuNPs remains essential for cancer theranostics.…”
Section: Resultsmentioning
confidence: 99%
“…63 Cancer seeking molecules conjugated gold nanorods are potential PA targeting imaging agents for cancer detection in vivo because their strong absorption of light and characters of plasmon resonance absorption and scatter in NIR. 64,65 Recently, a novel colloidal hybrid nanostructure with goldbased tripod architecture was designed and prepared for better targeted molecular PA imaging of tumor tissues in vivo.…”
Section: Size and Shape Of Gold Nanoparticlementioning
confidence: 99%